Faktor yang Meningkatkan Kepatuhan Perawat dalam Penerapan Ventilator Bundle : Kajian Literatur - Erdiana Rhamalia; Inge Dhamanti (LPPM Hang Tuah Pekanbaru, 2024)
Background: Ventilator-associated Pneumonia (VAP) is a pneumonia infection after 48 hours of mechanical ventilation. According to WHO in 2018, the incidence of VAP in mechanically ventilated patients is around 22.8% in the world and accounts for 86% of nosocomial infections with the global incidence of VAP increasing between 9-27%. Even though it is standardized, the number of nurses compliance with ventilator bundles is low. Aim: to determine the factors that increase nurse compliance in implementing the ventilator bundle. Method: The research was conducted in June-September 2024. The research used a literature review spanning the years 2020-2024. The search used the PubMed and Google Scholar databases with the PRISMA search flow. Results: the increase in nurse compliance in implementing the ventilator bundle had an average of 22.56%. Some of the research locations studied were in various hospitals around the world, such as Brazil, Hungary, Argentina and India. The dominant research design or design in the study is cross-sectional. In the study, it was found that nurses' knowledge and education based on a combination of gamification, debriefing and simulation methods related to the ventilator bundle were internal factors. Apart from that, monitoring the ventilator bundle checklist is an environmental characteristic of external factors. Conclusion: internal factors that increase nurse compliance are ventilator bundle knowledge and education, while external factors are environmental characteristics in the form of a ventilator bundle checklist, so they need to be implemented to achieve compliance according to standards.